Preparation of Polyacrylonitrile/Ni-MOF electrospun nanofiber as an efficient fiber coating material for headspace solid-phase microextraction of diazinon and chlorpyrifos followed by CD-IMS analysis. (15th July 2021) - Amini, Shima; Ebrahimzadeh, Homeira; Seidi, Shahram; Jalilian, Niloofar
Highlights: A novel electrospun polyacrylonitrile/Ni-MOF composite nanofibers were synthesized. Ni-MOF improved porosity and extraction efficiency of PAN/Ni-MOF nanofibers. The method provided low LODs and good recoveries for measuring diazinon and chlorpyrifos. This method is environmentally friendly due to the thermal desorption step. Abstract: Herein, an electrospun polyacrylonitrile/nickel-based metal–organic framework nanocomposite (PAN/Ni-MOF) coating on a stainless steel wire was synthesized and employed as a novel nanosorbent for headspace solid-phase microextraction (HS-SPME) of organophosphorus pesticides (OPPs), diazinon (DIZ), and chlorpyrifos (CPS) from the diverse aqueous media followed by corona discharge ion mobility spectrometry (CD-IMS). Under the optimum experimental conditions, the calibration plots were linear in the range of 1.0–250.0 ng mL −1 for DIZ and 0.5–300.0 ng mL −1 for CPS with r 2  > 0.999. The detection limits (S/N = 3) were 0.3 and 0.2 ng mL −1 for DIZ and CPS, respectively. The intra-day relative standard deviations (RSDs%) (n = 5) at the concentration levels of 20.0, 40.0, and 100.0 ng mL −1 were ≤ 5.2%. To investigate the extraction efficiency, PAN/Ni-MOF was employed to analyze various juice samples, including orange, apple, and grape juices, and in three water samples where it led to good recoveries ranged between 87% and 98%.